Está en la página 1de 3

# GOITIA, Amadeo Rafael - 1° “B” IEM – Legajo: 21045

## 2𝑥 6 +2𝑥 5 −3𝑥 2 −3𝑥

1) 𝑓(𝑥) = 𝑥 2 −1
a) 𝒙𝟏 = 𝟎
𝟒 𝟑
𝒙𝟐 = √
𝟐

𝟒 𝟑
𝒙𝟑 = − √
𝟐

b)
c) AV:
2𝑥 6 + 2𝑥 5 − 3𝑥 2 − 3𝑥 (𝑥)(𝑥+1)(2𝑥 4 −3)
lim = lim =∞
𝑥→1 𝑥2 − 1 𝑥→1 (𝑥 + 1)(𝑥 − 1)

## (𝑥)(𝑥 +1)(2𝑥 4 −3) 𝟏

lim =−
𝑥→−1 (𝑥 + 1)(𝑥 − 1) 𝟐

## 𝑑𝑦 2𝑥 6 +2𝑥 5 −3𝑥 2 −3𝑥 8𝑥 5 −10𝑥 4 +3

d) 𝑑𝑥
( 𝑥 2 −1
) = 𝑥 2 −2𝑥+1
= 0 → 𝒙 ≈ −𝟎. 𝟔𝟔𝟓𝟐𝟎𝟐𝟖𝟕𝟗𝟑𝟖𝟕𝟗
e)
𝑦 = −3𝑥 + 4
(𝑦 − 𝑦𝑜 ) = 𝑚(𝑥 − 𝑥𝑜)

8𝑥 5 − 10𝑥 4 + 3
= −3 → 𝒙 ≈ −𝟎. 𝟗𝟓𝟏𝟑𝟎𝟒𝟔𝟕𝟖𝟎𝟏𝟐𝟗
𝑥 2 − 2𝑥 + 1

## (𝑦 + 0.6640153438648) = −3(𝑥 + 0.9513046780129)

GOITIA, Amadeo Rafael - 1° “B” IEM – Legajo: 21045

28539140340387𝑥
𝑦 = −3𝑥 − − 0.6640153438648
10000000000000
58539140340387𝑥
𝑦=− − 0.6640153438648
10000000000000

f)
3
𝑑 2 𝑦 2𝑥 6 +2𝑥 5 −3𝑥 2 −3𝑥 2(3−20𝑥 +30𝑥 4 −12𝑥 5 ) 2(12𝑥
5
−30𝑥 4 +20𝑥 3 −3)
g) 𝑑𝑥 2
( 𝑥 2 −1
) = 1−3𝑥+3𝑥 2 −𝑥 3
=− 1−3𝑥+3𝑥 2 −𝑥 3
=
0→ 𝒙 ≈ 𝟏. 𝟑𝟏𝟗𝟎𝟒𝟑𝟖𝟑𝟑𝟐𝟖𝟓𝟗

## (−∞; 1) → 0 → 𝑦´´(0) = 6 > 0 → 𝑐𝑜𝑛𝑐𝑎𝑣𝑎

6 6 4926
(1; 1.3190438332859) → → 𝑦´´ ( ) = − < 0 → 𝑐𝑜𝑛𝑣𝑒𝑥𝑎
5 5 25

## (1.3190438332859; ∞) → 2 → 𝑦´´(2) = 122 > 0 → 𝑐𝑜𝑛𝑐𝑎𝑣𝑎

2) 𝑥 ∗ 𝑦 = 𝑆
(𝑥 − 2) ∗ (𝑦 − 3) = 24
3𝑥 + 18
𝑦=
𝑥−2

3𝑥 + 18
𝑥∗ =𝑆
𝑥−2

𝑑𝑦 3𝑥 + 18 3𝑥 2 − 12𝑥 − 36
(𝑥 ∗ )= = 0 → 𝒙𝟏 = −𝟐 ; 𝒙𝟐 = 𝟔
𝑑𝑥 𝑥−2 𝑥 2 − 4𝑥 + 4
GOITIA, Amadeo Rafael - 1° “B” IEM – Legajo: 21045